A Study Of Factors That Motivate Lower Rank Personnel In The Royal Malaysian Navy - Abdul, Asmayatim (2003)
This study involve the lower rank in the Royal Malaysian Navy (RMN) based in Lumut, Kuantan and Kuala Lumpur. The purpose of this study is to gain some understanding of factors that influence motivation among the lower rank personnel in the RMN. The respondents were selected randomly using the stratified sampling method to reflect true composition of the study population. The total of 307 samples were used in the analysis. The findings indicate that generally the motivation of the lower rank personnel in the RMN’s is more influenced by the intrinsic factors such as interesting job, promotion and career growth. Extrinsic factors such as job security, wages, organisation’s effort in welfare, interpersonal relationship and work environments are important in maintaining the satisfaction at work. Leader’s personal conduct and behaviour also showed significant influence on RMN’s lower rank personnel’s work behaviour. Leaders with high “budi” values are most likely to improve subordinates work effort. Good characteristics in leaders that conform to “budi” values such as tolerant, caring and cooperative would increase work motivation. Negative “budi” characteristics such as domineering, inconsiderate and arrogance will most likely to decrease work motivation. The overall level of patriotism is high among the RMN’s lower rank personnel but it has no significant effect on intrinsic motive. Perception on performance appraisal on the other hand indicates that it has significant negative effect on intrinsic motivation.